Three new species of Fergusonina Malloch gall-flies (Diptera: Fergusoninidae) from terminal leaf bud galls on Eucalyptus (Myrtaceae) in south-eastern Australia - Nelson, Leigh A.; Scheffer, Sonja J.; Yeates, David K. (Zootaxa, 2011)
Three new species of Fergusonina (Diptera: Fergusoninidae) flies are described from terminal leaf bud galls on Eucalyptus L’Hér. from south eastern Australia. Fergusonina omlandi Nelson and Yeates sp. nov. is the first species of fly from the genus Fergusonina to be described from the Eucalyptus pauciflora Sieb. ex Spreng. (Snow Gum) species complex; although another two species occur in sympatry on this host at higher elevations. Fergusonina omlandi sp. nov. can be distinguished from the latter by differences in adult size and markings on the mesonotum and morphology of the dorsal shield of the larva. The other new species, Fergusonina williamensis Nelson and Yeates sp. nov. and Fergusonina thornhilli Nelson and Yeates sp. nov. are the first flies to be described from Eucalyptus baxteri (Benth.) Maiden & Blakely and Eucalyptus dalrympleana Maiden, respectively. These two species can be distinguished from all other described Fergusonina by host specificity, adult colour and setation and morphology of the dorsal shield.